Reactions of Zn2+, Cd2+ and Hg2+ with Free Adenine - Hamada, Yahia Z.; Burkey, Theodore; Waddell, Emanuel; Aitha, Mahesh; Phambu, Nsoki (Journal of Applied Solution Chemistry and Modeling, 2013)
We are reporting the fluorescence quenching, IR, Raman, 1H-NMR, and potentiometric studies for the Zn2+:adenine and the Cd2+:adenine systems under ambient conditions. IR and Raman spectra suggest that Zn2+ and Cd2+ interact with adenine but the modes of interaction differ. Fluorescence spectra indicate that the interaction involving Zn2+ is more favorable than that of Cd2+, and this effect is due to the difference in ionic radii. 1H-NMR, potentiometry, and speciation diagrams indicate the formation of strong metal ion adenine complexes. Potentiometric titrations of the heavier member of group 12 metals (Hg2+) show similar results to that of Zn2+ and Cd2+. Some differences in the 1H-NMR experiments appeared between both (Zn2+ and Cd2+) compared to that of Hg2+. Due to the fluorescence quenching of adenine, adenine can be used as a sensor of Zn2+ and Cd2+.